O-107 Integrating advance care planning into legal practice: Development of an ACP legal toolkit. (1st September 2015) - Douglas, Maureen L; Fassbender, Konrad; Simon, Jessica E; Biondo, Patricia D; Wasylenko, Eric; Ries, Nola M
Abstract : Background: The medical and legal fields coalesce around advance care planning (ACP). There is an opportunity for the legal community to be a stronger partner in the uptake of ACP beyond advance directive completion. Analysis is required of gaps in resources and supports to help lawyers promote and be engaged in ACP conversations. Aim: To develop an ACP legal toolkit to help lawyers promote and be engaged in ACP communication. Methods: Two workshops for researchers (5), lawyers (17), clinicians (3), and other stakeholders (8) from the legal and medical communities are being held in Alberta, Canada to discuss lawyers' roles, needs and barriers regarding ACP. These workshops will bring together key stakeholder groups who have been working in parallel and have a keen interest in improving the uptake of ACP, but have otherwise had few opportunities to connect e.g. the Canadian Bar Association, Legal Aid, legal education organisations, academics, government representatives, and patient advisors. The intended outcomes of the meetings are to establish the contents of an ACP legal toolkit, establish roles and responsibilities around compiling the toolkit, and to develop a plan for dissemination. A core group (10) from these meetings will attend a follow up meeting about implementation. Results: A description of the meeting results, the ACP legal toolkit, its compilation, development and dissemination will be presented